Diminished Capsule Exacerbates Virulence, Blood–Brain Barrier Penetration, Intracellular Persistence, and Antibiotic Evasion of Hyperhemolytic Group B Streptococci. (2nd January 2018) - Gendrin, Claire; Merillat, Sean; Vornhagen, Jay; Coleman, Michelle; Armistead, Blair; Ngo, Lisa; Aggarwal, Anjali; Quach, Phoenicia; Berrigan, Jacob; Rajagopal, Lakshmi
Abstract : Hyperhemolytic group B streptococci trade capsule for increased virulence, blood–brain barrier penetration, intracellular persistence, and antibiotic evasion. Abstract: Group B streptococci (GBS) are encapsulated, β-hemolytic bacteria that are a common cause of infections in human newborns and certain adults. Two factors important for GBS virulence are the sialic acid capsular polysaccharide that promotes immune evasion and the hemolytic pigment that induces host cell cytotoxcity. These virulence factors are often oppositely regulated by the CovR/CovS two-component system. Clinical GBS strains exhibiting hyperhemolysis and low capsule due to pathoadaptive covR/S mutations have been isolated from patients. Given the importance of capsule to GBS virulence, we predicted that a decrease or loss of capsule would attenuate the virulence of covR/S mutants. Surprisingly, hyperhemolytic GBS with low or no capsule exhibit increased virulence, intracellular persistence, and blood–brain barrier penetration, which was independent of a Trojan horse mechanism of barrier penetration. Additionally, intracellular persistence enabled both hemolytic and hyperhemolytic GBS to evade antibiotics routinely used to treat these infections. The finding that diminished capsule expression promotes GBS virulence, intracellular persistence, and antibiotic evasion has important implications for sustained antibiotic therapy and efficacy of capsule-based vaccines.